Short Communication: Acute toxicity study of plantaricin from Lactobacillus plantarum S34 and its antibacterial activity - Arido Yugovelman Ahaddin; Sri Budiarti; Apon Zaenal Mustopa; Huda S Darusman; Lita Triratna (Society for Indonesian Biodiversity, 2021)
Abstract. Ahaddin AY, Budiarti S, Mustopa AZ, Darusman HS, Triratna L. 2021. Short Communication: Acute toxicity study of plantaricin from Lactobacillus plantarum S34 and its antibacterial activity. Biodiversitas 22: 227-232. Lactobacillus plantarum S34 belongs to the Lactobacilli class produces a bacteriocin called plantaricin. Bacteriocins are well known as active compounds that inhibit bacterial growth. This study was conducted to determine the antimicrobial activity of plantaricin S34 and its safety profile in the ddY mouse animal models. Plantaricin 34 from the crude extract was identified using Tricine SDS-PAGE. Antimicrobial activity was observed using disk diffusion against EPEC K1.1, S. aureus, S. typhosa, S typhimurium, and Proteus sp. The safety assessment showed that crude extract of plantaricin S34 did not cause any abnormalities to experimental mice even after being administrated with 5000 mg/kg BB. The identification of plantaricin S34 showed an active molecule at 7.34 kDa and had an activity to inhibit the pathogens used in this study. The blood analysis showed that the hematological and biochemical blood properties were in the normal range. Histopathological examination showed no damage to the intestine, liver, and kidneys. Thus, the crude extract of plantaricin S34 is active as an antimicrobial agent without any toxicity effects.